POTENTIALS AND ETHICS OF STEM CELL-DERIVED GAMETES: EXPERT VIEWS FROM MALAYSIA - Isa, Noor Munirah; Saad, Nur Syafiqah (Jurnal 'Ulwan, 2023)
Stem cell-derived gametes (SCDGs) offer a promising solution for addressing infertility and advancing reproductive technologies. Nevertheless, developing this type of gamete in Malaysia necessitates careful consideration of ethical concerns. This study discusses the expert views on the potential of the application and concerns that might arise if this technology were implemented in Malaysia. It also analyzes their perspectives on whether technology can be allowed in Islam. Library research and interviews with experts in stem cell research and Islamic studies were conducted. This study found that the experts are positive about developing stem cell-derived gametes as this application holds great potential for addressing reproductive issues in the country. It could be allowed in Islam. However, it is necessary to establish strict rules to address ethical concerns and ensure responsible development and use. Continued research and collaboration among scientists, religious scholars, and policymakers are necessary to ensure its safe and ethical implementation.